Agro-forestry waste management- A review. (January 2022) - Gupta, Juhi; Kumari, Moni; Mishra, Arti; Swati,; Akram, Mohd; Thakur, Indu Shekhar
Abstract: Agroforestry, an integration of farming system with woody perennials leads to the generation of potential agroforestry residues. The conventional treatment of agroforestry waste includes landfilling, thermal management, and decomposition which is accompanied with their own share of disadvantages. The ample amount of residues and products needs effective management to reap the economic and environmental benefits. The channel of waste collection, transportation, and recycle or valorization into products like biofuel, fertilizers, biochar, industrial chemicals is essential to maintain a circular sustainable bioeconomy. Global market value of biowaste to bioenergy (BtB) technology is roughly US $25.32 billion and is projected to enhance to US $40 billion by 2023. Employment of an appropriate pretreatment technology such as fermentation, hydrolysis, gasification etc. is going to elevate the degree of valorization along with surpassing the mobilization barrier. The sustainability assessment of the management process can be achieved with multiple models including technoeconomic analysis, life cycle assessment and multi criteria approach which are dependent on both hard and soft indices. Additionally, the loopholes of the agroforestry sectors would be managed by the introduction of appropriate policies which are undertaken globally by the Orlando and Lugo declarations, food and agriculture organization, Millennium Development Goals, Global Research Alliance and Guidelines for Sustainable Agriculture and Rural Development. The present review envisaged the agroforestry waste management strategy and its sustainability assessment primarily based upon Social, Economic and Environmental parameters without tormenting the future generations. Graphical abstract: Image 1 Highlights: The valorization of agroforestry waste for value-added products in biorefineries. Bioeconomic potential along with the discussion of sustainability indices. Existing laws and policies for effective agroforestry waste management. Social, economic, and environmental aspects of waste management are studied.